Fundamental studies on tribolayers created by lubricating pastes with new additive packages. Issue 1 (9th January 2017) - Busch, Christian; Weber, Simon; Schneider, Reinhardt
Abstract : Purpose: The purpose of this paper, an R&D project, is to select Globally Harmonized System of Classification and Labeling of Chemicals (GHS)-unclassified white solid lubricants for formulating special lubricating oils, greases and pastes to prevent tribological systems against fretting wear. Design/methodology/approach: The scientific methodology reads as follows: market research to select appropriate additives according to the purpose of the R&D project; screening tests to determine the technical performance of the additives; advanced technical studies and tests to validate the technical performance of the lubricating additives; determination of the reaction layers; and clarification of the build-up mechanism of the reaction layers (practical tests). Findings: The findings of the R&D project can be summarized as follows: the selected white solid lubricants perform in lubricating oils, greases and pastes highly effective against fretting wear. The performance could be shown on the basis of representative test results and highlights its advantages compared to the state of the art. Research limitations/implications: The research team faced some challenges during the R&D project – the unsuitability of standard test measurements as well as DIN, ISO and ASTM test parameters led to limitations and increased effort. Originality/value: The motivation and main target to conduct the R&D project was to increase the consumer and operator safety by using unclassified (GHS) high performance lubricants. The findings of the project show clearly that the tasks could be fulfilled. Special, unclassified (GHS) selected white solid lubricants are able to form a reaction layer on metal surfaces and separate effectively the surfaces within the tribological system. No fretting wear accrued. The consumer can gain substantial benefits on the economical side as well as on the ecological side.